Estudo da atividade antibacteriana, físico químicas farmacocinéticas e toxicológicas de novos compostos derivados de pirazolina - Mota, Augusto Dias da (2022)
Pseudomonas aeruginosa is an opportunistic bacterium that rarely causes infection in healthy people. However, it is among the main agents in nosocomial infections, with high rates of morbidity and mortality due to its multidrug resistance (MDR). This microorganism is capable of triggering serious infections in immunocompromised individuals, the most susceptible being those hospitalized in intensive care units, burn patients and cystic fibrosis patients.Although there are many classes of antibiotics available for treatment, infections by multidrug-resistant strains are increasingly common, especially in the hospital environment. These sites, in addition to the circulation of susceptible and immunocompromised individuals, present favorable conditions for the transmission and selective pressure of the strains, favoring the emergence of multidrug-resistant isolates. Carbapenem-resistant P. aeruginosa were included in the World Health Organization (WHO) list of three species of bacteria in critical need for the development of new antibiotics. Heterocyclic compounds derived from pyrazolines have been synthesized and used in studies due to their characteristics and various pharmacological properties. Computational tools (in silico) have been proposed in order to reduce the time and high costs involved in this process. These technologies allow the association of computational predictions with pre-clinical laboratory tests (in vitro and in vivo), making these models cost-effective in drug research and development. In view of the urgent need to discover new antibiotics or therapeutic alternatives for the treatment of multidrug-resistant infections caused by this pathogen, the present study aimed to evaluate the antibacterial activity of seven new compounds derived from pyrazolines in multidrug-resistant clinical isolates of P. aeruginosa and to study their properties. physicochemical, pharmacokinetic and toxicological properties using in silico tools. To evaluate the antibacterial activity of the drugs, the determination of the minimum inhibitory concentration (MIC) was performed. The cytotoxicity of the compounds was evaluated in assays with the fibroblast cell line (VERO). The pyrazoline compounds that showed activity had a MIC of 0.2 mg/mL compared to clinical isolates and IC50 values that ranged from 0.0081mg/mL to 0.4577mg/mL. Regarding the pharmacokinetic and toxicological results (in silico), the analyzed compounds did not violate the rule of five, established by Lipinski. In addition to these parameters, the number of rotational bonds was less than 10 (between 3 and 4) and the TPSA was less than 140 Å (65.79), which confirmed a good oral bioavailability of the analyzed compounds. The in silico prediction and their respective antimicrobial activities of the molecules analyzed here, with reservations and possible molecular rearrangements, allows us to suggest them as potential candidates for drugs to be used orally with good permeability through biological membranes and high absorption by the gastrointestinal route.